(untitled) (Research, Society and Development, 2023)
The present study aimed to evaluate the surface quality of reused wood, analyzing whether the behavior and characteristics indicated in the production of furniture are still maintained after use, in order to indicate appropriate uses and applications. In the furniture sector, the better the machined surface, the better the quality of the product. Two wood boards of Maçaranduba (Manilkara sp.) and Sucupira (Pterodon sp.) were then manually planed longitudinally and tangentially, considering the slow and fast machining speeds for each face, and the evaluation of the feed and speed speeds advancement per tooth. The relationship between feed speed and surface finish quality was observed, since faces machined at high speed presented a thick finish, obtaining 11.10 m.min-1 and 7.09 m.min-1 in feed speed for, respectively, Maçaranduba and Sucupira. The faces machined at slow speed showed medium quality of finish, less roughness and better quality of the planed surface according to the ASTM D 1666-22 standard when presenting 3.17 m.min-1 and 2.79 m.min-1 at speed of advance to, respectively, Maçaranduba and Sucupira. It was also noted that the faces that have a thick finish and, consequently, a higher feed speed per tooth, are subject to rework in order to achieve the necessary quality for furniture manufacturing. In view of this, it was verified that Maçaranduba machined slowly presented excellent surface quality, responding positively to the objective of the exposed work.